Assessing Knowledge and Attitude of Dental Patients regarding the Use of Dental Implants: A Survey-Based Research - Abdulrahman Alajlan; Aryaf Alhoumaidan; Abeer Ettesh; Mazen Doumani (Hindawi Limited, 2019)
Aim. The purpose of this study was to assess the level of knowledge, attitude, and source of information regarding the use of dental implants as treatment option compared to other conventional treatment modalities. Materials and Methods. A descriptive cross sectional study among adult dental patients attended dental clinics of College of Dentistry, Qassim University. The level of knowledge, source of information, and attitude regarding the use of dental implants were evaluated through standardized self-explanatory questionnaires which were handed to the patient during their regular dental visits. 200 patients were selected randomly to be included in this survey. Results. Among the 200 participants included in this study, 91.5% of the respondents heard about implants and their source of information were friends (45.5%), 38% of the respondents had no idea about the oral hygiene for the care of the implants compared with natural teeth, 28.5% of the respondents expected them to last between 10 and 20 years, and 48.5% of the respondents believed that dental implants have no effects on the systemic health and there was nonsignificant difference between males and females. Conclusion. The survey concluded that an acceptable level of awareness regarding using dental implants as a treatment option for replacing missing teeth, with friends being the main source of information.